UNDERSTANDING CULTURAL ASSORTMENT: A CONCEPTUAL STUDY - Rajendiran, Dr. Rajalakshmi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Cultural studies is an interdisciplinary field, concerned with the roles of social institution in the shapings of culture and is interested in the profess by which power relations organize cultural artefacts. It looks at the popular culture and is interested in every day life components such as food, habits, music, sports events, cinema etc., which have been dismissed as underlings and unworthy of academic studies. It influences the social relationships, bestows the meanings and values of artifacts of culture. In India, after economic liberalization, consumption has been seen as the marker of identity. Hence commodities are identities of lifestyle and consumption begin after the actual act of shopping. Culture amounts to the life ways of the socially connected group of people sharing a common view of the world. So culture includes language, ideas, norms, beliefs, customs, codes, institutions, tools, techniques, works of art, rituals, ceremonies, and basically culture is a combination of how people think, act and what they own. The objective of this study is to integrate the different levels of culture by explicitly recognizing the features and types of culture, examining their similarities and differences. Understanding a wider array of forms of culture might promote new views about what culture is and by studying cultural influences, one can understand the domains of culture more broadly. This paper is a conceptual study and therefore extends the current understanding of not only examining multiple levels of culture but also specifying conditions under which certain levels of culture dominate. Such an approach informs the researchers and practitioners about the generalizability or universality of theories and techniques across national, organizational, and professional borders.